Effects of Chlorella vulgaris supplementation on dietary digestibility, intestinal morphology and microbiota, growth performance and survival of red tilapia hybrid (Oreochromis spp.) - Talba, Ahmad Muhammad (2018)
While the global aquaculture production is increasing, outbreak of diseases and the stagnation of wild fish catch which is the main source of protein to the aquaculture feed industry are the major impending drawbacks. There are several claims on the roles of microalgae in fish nutrition and health, with limited information on the effects of its supplementation on dietary digestibility as well as an in-depth effect on fish health. To explore these; a feeding trial using Chlorella vulgaris was carried out. The study was aimed at investigating the effects of C. vulgaris supplementation on the dietary digestibility and its effects on intestinal function, morphology and microbiome alongside growth performance and haemato-biochemical parameters. A commercial diet (base diet) was supplemented with C. vulgaris at 0, 1, 3, and 5% kg-1 (control, C. vulgaris supplemented feed I, II and III, respectively). A total of 84 red hybrid tilapia (105 ± 7 g, mean ± SE) were randomly distributed into 12 tanks (three plicate per treatment group) with 21 fish in each treatment group (7 fish/tank). The fish were fed the supplemented diet for a 21-day feeding trial. Faeces were collected twice daily, which was analysed at the end of the experiment. For the second phase of the experiment, the design described above was used. Four hundred and fifty-six tilapia were randomly distributed as described earlier. Each experimental feed was fed to the appropriate treatment group of fish for 12 weeks, with sampling carried out at 30 days intervals. The result of digestibility trial showed that C. vulgaris supplementation at all the levels (1, 3, and 5%), significantly improved the apparent digestibility coefficient values for dry matter and protein which was also associated with increase in supplementation. At the end of the second phase experiment, the results of performance trial showed a positive influence of the supplementation and duration of feeding on growth, feed utilization and haemato-biochemical parameters. Simultaneous and significant influence of supplementation and duration was observed on weight gain, average growth rate, mean daily feed intake total plasma protein, albumin, globulin, red blood cell counts and packed cell volume. Similarly, simultaneous and significant influence of supplementation levels and duration of feeding was noted in the intestinal morphology, alongside an increase in the inducible nitric oxide synthase (iNOS) in fish fed Chlorella supplemented feed. Following challenge trial with Streptococcus iniae, significantly higher cumulative survival was seen in fish fed diets supplemented with Chlorella. Next generation sequencing of the 16S rRNA biomarker gene V3-V4 region of the gut microbiota revealed that 97.65% of the bacteria belonged to five phyla; the usobacteria (53.84 %), Bacteroidetes (33.99%), Proteobacteria (5.56%), Verrucomicrobia (3.04%) and Firmicutes (1.22%). Both the control and treatment groups appeared to have similar microbial community structural composition and core gut microbiome. Whereas, the intestinal microbiota of fish fed treatment diets had microbial biomarkers dominated by Firmicutes as opposing to the Cyanobacteria of the control fish. Therefore, the current study revealed the influence of Chlorella vulgaris supplemented feed on fish gut microbiota, intestinal health and growth performance of red hybrid tilapia.